Relationship of Leadership Behavior with School Effectiveness: An Evidence of Public Primary Schools - Ehsan Mahmood,; Javid Iqbal,; Saadia Adnan, (JELM, 2023)
This study intended to examine relationship between public primary school heads’ leadership behaviors and school effectiveness indicators. Proper permission from Punjab Education Department was obtained to conduct this research study in Public Primary Schools. Study employed stratified random sampling technique to select 480 heads and their subordinate teachers from eight districts of the Punjab. Survey approach was considered appropriate to collect data for this co-relational study. An Urdu version of Multifactor Leadership Questionnaire (5X-Short) developed by Avolio and Bass (1995) was utilized in both leader (Head) and rater (Teacher) forms to determine heads’ leadership behaviors. School Effectiveness Measurement Questionnaire developed by Iqbal (2005) was administered to measure school effectiveness. Overall, 467 heads and their subordinate 1296 teachers rated the questionnaires. The study results portrayed considerable relationship between transformational leadership behaviors and indicators of school effectiveness. Specifically, ‘idealized influence-behavior’ showed significant relationship with indicators of school effectiveness. Only single factor of the transactional leadership ‘contingent reward’ showed significant relationship with indicators of school effectiveness. ‘Management by exception-passive’ the component of transactional leadership and ‘Laissez-faire leadership’ showed negative relationship with school effectiveness indicators.